2020
DOI: 10.1016/j.heliyon.2020.e04711
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of black seed oil supplementation on chronic obstructive pulmonary disease patients: A randomized controlled double blind clinical trial

Abstract: This study sought to examine whether supplementation of Black Seed Oil (BSO) can improve pulmonary function tests (PFTs), inflammation, and oxidant-antioxidant markers in COPD patients. The study involved 100 patients of mild to moderate COPD divided randomly into 2 groups who were appointed to receive standard medication only ( control group ) or with additional Black Seed Oil ( BSO group ). They were assessed initially and after 3 months, 44 patients responded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 60 publications
(78 reference statements)
0
18
0
Order By: Relevance
“…The results of this trial showed statistically significant increase in the values of pulmonary function tests in comparison to the control group. IL-6 and TNF-α levels were also found to be decreased significantly in participants of BSO group when compared to the control group after the completion of the trial 40 .…”
Section: Nigella Sativa In Preventing Inflammation In Asthma and Copdmentioning
confidence: 85%
“…The results of this trial showed statistically significant increase in the values of pulmonary function tests in comparison to the control group. IL-6 and TNF-α levels were also found to be decreased significantly in participants of BSO group when compared to the control group after the completion of the trial 40 .…”
Section: Nigella Sativa In Preventing Inflammation In Asthma and Copdmentioning
confidence: 85%
“…28 Ingestion of coldpressed black seed oil daily for twelve weeks significantly reduced plasma levels of TNF-α (I: −35%, C: −22%, p <0.001) and IL-6 (I: 38%, C: 28%, p = nr). 25 Daily supplementation with protein bars for nine weeks showed a tendency toward treatment effect on plasma CRP (Δ mean: 3.9, p=0.14). 19 No significant effect was found on blood lymphocyte count after eight weeks of daily nutritional supplementation.…”
Section: Inflammationmentioning
confidence: 95%
“…Extracted data are summarized in Table 2 (and an extended version is included as a Supplementary File: Table S2). The following interventions were studied in the included trials: protein supplementation, 19 beetroot juice, [20][21][22] increased fruit and vegetable intake, 23,24 black seed oil, 25 Tualang honey, 26 Chlorella vulgaris extract, 27 whey-peptide containing nutritional drink, 28 and finally increased macronutrient intake. [29][30][31] All participants were adults with COPD, mostly aged 40 years and above.…”
Section: Selection Process and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations